OPTICAL PROPERTIES OF SOLID SOLUTIONS (FeIn2S4)(1-x)(In2S3)x - M. A. Novikova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Single crystals of In2S3, FeIn2S4 compounds and their solid solutions (FeIn2S4)1- x (In2S3)x have been grown by directional crystallization of the melt (vertical Bridgman method). Transmission spectra of the grown crystals in the intrinsic absorption edge region were investigated. Band gap width ( Eg ) and its concentration dependence have been determined on the measured spectra. It is established, that band gap width Eg changes nonlinearly with composition x .